2020
DOI: 10.1007/s11661-020-05875-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yttrium Additions in Relation to Oxygen Content on Glass Formation in the Zr50Cu40Al10 Alloy

Abstract: The effect of yttrium additions on the glass formation of the Zr50Cu40Al10 alloy with high oxygen content was investigated. Unlike other reports showing the positive effect of alloying Zr-based alloys with a few percent of rare earth elements, we examined the Y-to-oxygen ratios. As calculated, a stoichiometric amount of yttrium (2808 at ppm) is required to bind all the oxygen (4212 at ppm) to form the Y2O3. Additionally, the influence of half (1404 at ppm) and double stoichiometric (5616 at ppm) levels of yttr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…In our previous works, the oxygen content in the Zr50Cu40Al10 alloy was 918 wt. ppm [19,36]. Here, a slightly higher value (988 wt.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…In our previous works, the oxygen content in the Zr50Cu40Al10 alloy was 918 wt. ppm [19,36]. Here, a slightly higher value (988 wt.…”
Section: Resultsmentioning
confidence: 75%
“…However, the biggest disadvantage of this method is heat distribution disturbance caused by potential turbulent liquid flow during casting. Laws et al [42] showed that the real critical casting diameter obtained from parallel-edged molds should be lower than those from conical molds, however, our previous works show a reverse correlation [19,36,43]. This effect can be stronger in the case of inclusion occurrence (e.g.…”
Section: A Determining the Critical Diametermentioning
confidence: 63%
See 3 more Smart Citations